Study the Effect of Educational Groups’ Activities on Knowledge and Continuous Development of Competencies and Empowerment of Professional teachers in Parsian Department of Education - Ranjbar, Mokhtar; Pasalar, Zeynab (IJRDO- Journal of Educational Research, 2017)
The main purpose of this study is to investigate the effect of educational groups’ activities onKnowledge and Continuous Development of Competencies and Empowerment of Professionalteachers in Parsian department of education. This research is applied and descriptive-analyticalone. The population of the study consists of 1,845 from all teachers and staffs under the supervisionof Parsian Department of Education. In this research, simple random sampling was used todetermine the sample. Based on the Morgan’s table and Cochran’s formula, 317 people wereselected as the statistical sample. The classes of this statistical sample included 150 first-year highschool students and 167 from secondary high school students. Research instruments were threeresearcher-made educational questionnaires, knowledge and continuous developmentquestionnaire, and standard questionnaire for professional empowerment of teachers(Mollaeenejad, 2012). To evaluate the validity of the variables, the method of cluster analysis wasused. Cronbach’s alpha was used to measure its reliability and it was 0.88. The linear andmultivariate regression analysis methods were used to analyze the hypotheses test. SPSS softwarewas used for analysis. In general, based on the test conducted and the results obtained fromknowledge and continuous development of the competencies of the professional empowerment ofteachers in Parsian department of education, it shows that the activities of the educational groupsand their components, knowledge and continuous development have positive effects on thecontinuing competencies of the professional empowerment of teachers in Parsian department ofeducation.